Pengaruh Pelatihan Dan Pendidikan, Pemanfaatan Teknologi Informasi, Dan Kompetensi Sumber Daya Manusia Terhadap Efektivitas Sistem Informasi Akuntansi Pada LPD Se Kecamatan Sukawati - Rustina, Ni Wayan Meiya Nitha; Yuniasih, Ni Wayan; Putra, I Putu Deddy Samtika (UNHI Press, 2025)
The Village Credit Institution is one of the financial institutions that has used an accounting information system in processing data and transactions. The utilization of accounting information systems within LPDs contributes to streamlining data processing for enhanced practicality among employees. This study seeks to investigate the impact of training and education, information technology utilization, and human resource proficiency on the efficacy of accounting information systems across LPDs in Sukawati District. The study population includes all employees from 33 LPDs within Sukawati District, totaling 281 individuals. A sample size of 111 participants was selected using purposive sampling, and the data was analyzed using multiple linear regression analysis techniques. The results indicate that training and education, the use of Information Technology, and human resource competence have a positive and significant effect on the effectiveness of the accounting information system. The use of information technology, especially the use of computers supported by internet networks, must always be improved in LPD. The use and maintenance of information technology must always be considered in order to facilitate employee work and reduce possible obstacles.